The natural-philosophical image of the Cosmos (Universe) according to Grigor Tatevatsi - Zaqaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
As a follower of the Armenian tradition of Aristotelianism, St. Grigor Tatevatsi (1346-1409) mainly relies on the ideas of Aristotle regarding nature and the Medieval theological literature when expressing his understandings about natural philosophy. Unlike other Armenian natural philosophers of previous centuries Tatevatsi highlights the «natural science» (natural cognition)'' in the system of knowledge. This means the importance of knowledge about the nature and such a change in cognitive attitude towards the earthly world that signifies the importance and necessity of empirical observations in the system of knowledge. In general Tatevatsi introduces such a picture of the Cosmos which corresponds to the principles and requests of the Medieval Christian worldview on one side and has universal character on the other because here the natural-philosophical (cosmological, astronomical, physical) understandings are tied up with those of metaphysical, theological, philosophical-anthropological and aesthetic-moral.
Keywords: Grigor Tatevatsi; Aristotelianism; Medieval Armenian Philosophy; Philosophy of Nature; Creationism; Cosmos; Qualitative ontology; Four elements; Space; Time